DNA Variations Within Yam Cultivars (Dioscorea Spp) as Indicated by RAPD Analysis - Mat Isa, Khairulhasni (2000)
A research on the DNA variations in eighteen yam cultivars from Malaysia and Japan was conducted using RAPD method in order to identify the cultivars and evaluate their genetic relationship. A preliminary identification of the cultivars was made using morphological characters of the plants. Ten primers, which were capable of producing PCR amplifications, were used in this research and were able to produce 515 amplification bands. Primer OPG-13 was found to be the best primer producing the most number and unambiguous fragments. All the ten primers were used for identifying and elucidating the genetic relationship among the cultivars. The dendrogram produced from the NTsys programme based on UPGMA, by using RAPD data showed that a close genetic relationship with a high percentage of similarity is between accession UPM DA 023 with accession UPM DA 024. Accession UPM DE 007 is a different species that is of Disocorea esculenta and thus genetically distant from the other accessions of Dioscorea alata. The tuber and leaf morphology of D. esculenta is also different from those of Dioscorea alata and indeed their genome is different too. The results of this research show that the RAPD technique can be used to identify the yam cultivars and to determine the genetic relationship among the cultivars. The genotype of all cultivars from Japan can be identified using only one primer, which is primer OPG-13. On the other hand, the identification of cultivars from Malaysia requires four primers, which are OPB-07, OPB-15, OPG-02 and OPG-13. In general, there is a close genetic relationship among yam cultivars found in Malaysia. However, these cultivars are different from Japan cultivars with the similarity index as low as 31.3%, indicating a distant relationship between them. RAPD is a very useful technique for the determination of genetic relationship and identification of plant cultivars. Such technique was successfully employed in genetic relationship and identification studies of D. alata and D. esculenta cultivars in Malaysia.